Reacting Quickly and Protecting Jobs : The Short-Term Impacts of the COVID-19 Lockdown on the Greek Labor Market - Betcherman, Gordon; Giannakopoulos, Nicholas; Laliotis, Ioannis; Pantelaiou, Ioanna; Testaverde, Mauro; Tzimas, Giannis (World Bank, Washington, DC, 2020)
This paper uses administrative, survey, and online vacancy data to analyze the short-term labor market impacts of the COVID-19 lockdown in Greece. The analysis finds that flows into unemployment have not increased; instead, separations were lower than would have been expected given trends in recent years. At the same time, employment was about 12 percent lower at the end of June than it would have been without the pandemic. The interrupted time-series and difference-in-differences estimates indicate that this was due to a dramatic slowdown in hiring during months when job creation typically peaks in normal years, mostly in tourism. Although the reasons for these patterns are not formally tested, the analysis suggests that the measures introduced to mitigate the effects of the crisis in Greece played an important role. These measures prohibited layoffs in industries affected by the crisis and tied the major form of income support to the maintenance of employment relationships.